PENGARUH PENGGUNAAN MODEL PROJECT BASED LEARNING TERHADAP KREATIVITAS PESERTA DIDIK SDIT AL-HUSNA KEC. WALANTAKA - Indira Maulidiarahma; A. Syachruroji; Encep Andriana (STKIP Persada Khatulistiwa Sintang, 2023)
This study aims to determine the effect of using the project based learning model on student creativity and to find out how much influence the use of project based learning models has on the creativity of SDIT Al-Husna students. The research method used is descriptive method with a quantitative approach. This research was conducted at SDIT Al-Husna with 30 respondents as the subject of research in class V students. based on the hypothesis testing that has been carried out using simple regression analysis shows that variable X (project based learning models) with variable Y (creativity) obtained an Fcount of 2.58 with Ftable 1.86, which means Fcount > Ftable then there is an influence a significant difference between variable X and variable Y. In addition, the magnitude of the effect is obtained from the product moment correlation test and the determinant coefficient which produces an Rxy value of 0.92 and is included in the category of